Optimization of the Bottom Profile of U-shape Oscillating Water Column - Tay, Chih Chia (2019)
U-Shape Oscillating Water Column (U-OWC) is found to have better efficiency than the conventional Oscillating Water Column (OWC). Although the overall shape of the OWC has been popularly researched in the field of wave energy, the studies on internal structure of the OWC is considerably lacking. The aim of this study was to determine the optimum bottom profile for the U-OWC structure that can deliver the best performance of U-OWC. ANSYS CFX simulation was performed on four U-OWC models with different bottom profile namely, flat, circular, 1:1 slope and 1:5 slope. The simulation results confirmed that the circular bottom profile has the greatest configuration to yield the highest air-discharge velocity, and power output. This was followed by 1:1 slope bottom profile, 1:5 slope bottom profile and flat bottom profile. Based on the simulated circular bottom profile U-OWC structure, prototype was fabricated to verify the simulation results. The percentage error between the simulated power output and the experimental power output was determined. Factors that were accounted for the error contribution were discussed. In overall, the identification of circular shape as the optimum design for the U-OWC bottom profile may help to increase the power efficiency of the future OWC structures as well as to provide supporting information for the future research projects on the parametric optimization of U-OWC.